Chapter 7 The challenge of creating a more diverse economics Lessons from the UCR minority pipeline project - Dymski, Gary A. (Taylor & Francis, 2019)
This paper reflects on the experience of the 1999-2002 minority pipeline program (MPP) at the University of California, Riverside. With support from the American Economic Association, the MPP identifi ed students of color interested in economics, let them explore economic issues aff ecting minority communities, and encouraged them to consider postgraduate work in economics. The MPP's successes and failures can be traced to the shifting balance in California's racialized political economy, especially a state ballot initiative forbidding the use of applicant race or ethnicity in University of California admission decisions, and to the transformation of economics itself, especially at the level of doctoral training. The MPP experience may be of relevance for other eff orts to increase racial/ethnic diversity in social science disciplines.